2023
DOI: 10.3389/fimmu.2023.1101390
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of parasite calreticulin

Abstract: Calreticulin from parasites and its vertebrate hosts share ~50% identity and many of its functions are equally conserved. However, the existing amino acid differences can affect its biological performance. Calreticulin plays an important role in Ca2+ homeostasis and as a chaperone involved in the correct folding of proteins within the endoplasmic reticulum. Outside the endoplasmic reticulum, calreticulin is involved in several immunological functions such as complement inhibition, enhancement of efferocytosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 152 publications
(225 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that CRTs are highly conserved in several parasite species, from protozoa ( Trypanosoma , Amoeba , and Leishmania ) to helminths ( Echinococcus , Opisthorchis viverrini , Brugia malayi and Necator americanus ), and play important roles in the adaptation of parasites to the hostile environments and escape from host immune responses ( 4 , 7 , 21 , 45 , 46 ). Our previous studies have determined that TsCRT can bind to human complement C1q and inhibit C1q-initiated classical complement activation to enable the parasite to evade host first-line immune attack ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that CRTs are highly conserved in several parasite species, from protozoa ( Trypanosoma , Amoeba , and Leishmania ) to helminths ( Echinococcus , Opisthorchis viverrini , Brugia malayi and Necator americanus ), and play important roles in the adaptation of parasites to the hostile environments and escape from host immune responses ( 4 , 7 , 21 , 45 , 46 ). Our previous studies have determined that TsCRT can bind to human complement C1q and inhibit C1q-initiated classical complement activation to enable the parasite to evade host first-line immune attack ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protozoa and helminths have both developed sophisticated strategies to evade immune attack by manipulating the host immune system during the long revolutionary process of parasite-host interplay. One of these strategies is to secrete proteins that target complement components to inhibit MAC formation ( 2 4 ). Calreticulin (CRT), for instance, is a key protein in immune evasion against complement attack.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calreticulin was suggested to be a key molecule in host–parasite interaction. In T. cruzi , helminths, and arthropod parasites, calreticulin interferes with C1q binding and complement system activation, and modulates the host cellular or humoral immune response (reviewed by [ 28 , 67 ]). Calreticulin is likely to play a prominent role in myxozoan virulence, as it does in other parasites [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, mAbs that can be employed in combination with conventional chemotherapy therapies to attack tumors by complementary modes of action. These mechanisms may include the production of antibodies by cytons of chemotherapeutic medical products that express anti-tumor immune responses [35] that may have been had diminished.…”
Section: Mechanism Of Actionmentioning
confidence: 99%